Pengembangan Media Pembelajaran Berbasis Android Menggunakan Ispring Suite 10 Pada Materi Turunan Fungsi Aljabar - Galleh Dwi Samudro; Ali Shodikin; Khafidhoh Nurul Aini (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
Mathematics is the basis for other sciences and students in schools from elementary school to college must learn and master it. But in reality, many students get the results of daily math tests under the minimum achievement criteria, especially on the derivative material of algebraic functions. This study has the aim of producing and developing appropriate learning media products which will then be tested for validity and practicality based on expert validation and student response questionnaires. This research is a research and development on 30 students of class XII PH 2 SMK Negeri 1 Lamongan. This research method uses the ADDIE model. results obtained in this study are as follows: 1) The results of the validity of the media obtained from the validation of media and learning materials, get an average rating of 87.5% in the "Very Valid" category, 2) The results of the student response questionnaire to determine the practicality of the media show a rating of 90.5% in the "Very Practical" category.